2018
DOI: 10.18433/jpps29905
|View full text |Cite
|
Sign up to set email alerts
|

Transport of AOPP-Albumin into Human Alveolar Epithelial A549 Cell

Abstract: AOPP-albumin is transported into alveolar epithelial cells through clathrin-mediated endocytosis, which may be important to prevent further ROS generation. This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…e results showed that, of the 50 patients, 25 patients had mild organophosphorus poisoning, accounting for 50%, 14 patients were moderately poisoned, accounting for 28%, and there were 11 severe patients. It has been found that, in AOPP patients, cascade effect is exerted by stimulating the secretion of inflammatory mediators such as CRP, causing systemic inflammatory response syndrome, and multiorgan failure appears in the early stage of the disease [18]. Adenosine triphosphate and reactive oxygen species produced by mitochondria play a key role in disease progression, and these two substances can also promote cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…e results showed that, of the 50 patients, 25 patients had mild organophosphorus poisoning, accounting for 50%, 14 patients were moderately poisoned, accounting for 28%, and there were 11 severe patients. It has been found that, in AOPP patients, cascade effect is exerted by stimulating the secretion of inflammatory mediators such as CRP, causing systemic inflammatory response syndrome, and multiorgan failure appears in the early stage of the disease [18]. Adenosine triphosphate and reactive oxygen species produced by mitochondria play a key role in disease progression, and these two substances can also promote cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the low-temperature (4°C) environment, sodium azide can affect cellular uptake by inhibiting the generation of intracellular ATP. Indomethacin is a COX/caveolinmediated endocytosis inhibitor [16,17]. Quercetin is a nonclathrin and non-caveolin-mediated endocytosis inhibitor [18].…”
Section: Study Of the Uptake Mechanismmentioning
confidence: 99%
“…Their level can reflect inflammation intensity, including activation of monocytes and neutrophils [ 8 ]. Accumulation of excessive AOPP during lung injury can initiate decreased lung fluid clearance, contributing to the disease progression [ 9 ].…”
Section: Introductionmentioning
confidence: 99%